Knowledge Management in Online Distance Education - Ubon, Adisorn Na; Kimble, Chris (Proceedings of the International Conference on Networked Learning, 2002)
Most organisations realise that "knowledge" is a strategic resource that gives them sustainable competitive advantage and helps them achieve long-term organisational goals. With the realization that knowledge is a core resource, organisations are now attempting to manage knowledge in a more systematic and more effective way. However, managing knowledge is not always an easy task. In particular contexts, such as online distance education, knowledge is distributed across both time and space and may be constrained by social, cultural and language differences. In such cases, the support of best practices in Knowledge Management (KM) could be problematic. This paper studies online distance education provision to identify the major problems that hinder KM practices. Focussing on online learning communities in which knowledge creation and knowledge sharing are essential elements, it tries to develop a set of guidelines to help overcome problems using tools and techniques from KM.